Takāful demand: a review of selected literature - Md Husin, Maizaitulaidawati; Haron, Razali (Emerald Publishing Limited, 2020)
This paper aims to provide a systematic review of literature on the demand for takaful (Islamic insurance) from articles published from January 2009 to June 2019. The review aims to synthesise and segment previously published research to identify the gaps and provide future research direction. A systematic review of the literature was conducted. Past research was analysed, and content comparisons based on research focus, context and methodology were evaluated. It was found that not much has been written and published on takaful demand in quality journals. The first two articles were published in 2009, but it was only in 2017 that coverage of the topic rapidly expanded. Although no article was found to have been published in 2018 on takaful demand, there was one published article on the topic in 2019. This paper also found that not much attention has been given to takaful demand from the corporate sector. The defined rule for document searching and selection excluded out-of-scope documents that might be relevant. Furthermore, as this paper concentrates exclusively on articles published in English journals, the possibility that other relevant works do appear elsewhere in a different language is not denied. Practical implications – Factors determining takaful demand are provided, and general directions are discussed, which managers can use to develop market share further. Such an extensive review of literature on takaful demand has not been done before. Other than revealing ambiguities, gaps and contradictions in the literature, this paper sketches an avenue for further research. It also provides information and guidance for other researchers wishing to embark on research on takaful demand.